Recyclable / redesigned aromatic nanofiber membrane / fiber and preparation method thereof

By dissolving aromatic fibers by organic strong alkali, methanol and dimethylsulfoxide, forming nanofiber solutions and dynamic bond self-assembly, the problems of deprotonation and recycling of aromatic nanofibers are solved, low-cost and rapid recycling are achieved, and the improvement of Its economy and environmental sustainability.

CN119194670APending Publication Date: 2024-12-27WUHAN TEXTILE UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411229011.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-03
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The deprotonation process of aromatic nanofibers is expensive and difficult to recover, limiting the economic feasibility and environmental sustainability of their large-scale applications.

Method used

Use organic strong alkali, methanol and dimethylsulfoxide to dissolve aromatic fibers to form nanofiber solutions, and obtain nanofiber membranes or fibers through scraping or wet spinning, and use dynamic bond self-assembly and solvent exchange to achieve low cost and rapid Recycle.

Benefits of technology

It realizes low-cost and rapid recycling of aromatic nanofibers, provides new ideas for recycling and utilization of some high-performance fibers, and reduces production costs and environmental burdens.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119194670A_ABST
    Figure CN119194670A_ABST
Patent Text Reader

Abstract

The invention relates to a recoverable / redesigned aromatic nanofiber membrane / fiber and a preparation method thereof, a recoverable / redesigned aromatic fiber product is constructed by adopting a membrane paving method and dynamic bond self-assembly, and the recovered aromatic nanofiber product can be re-spun and woven into a fabric. Common aromatic fibers are dissolved in a dimethyl sulfoxide solvent by destroying amido bonds in organic alkali, so that an aromatic nanofiber solution is obtained, and an aromatic nanofiber product is further formed through dynamic bond self-assembly. As the dynamic bond of the aromatic nanofiber product is reversible, the organic alkali can damage the molecular chain in the aromatic nanofiber membrane again, so that the aromatic nanofiber product is recycled again at low cost and low energy consumption; and the aromatic nanofiber solution recovered from the aromatic nanofiber can be used for redesign of aromatic nanofiber-based products in other forms.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a recyclable / redesigned aromatic nanofiber membrane / fiber and a preparation method thereof. Background Art

[0002] Aromatic fibers are a class of synthetic fibers containing aromatic ring structures, common ones include polyester (such as polyester), polyamide (such as nylon) and aromatics (such as Kevlar). These fibers have unique physical and chemical properties due to their aromatic ring structure, showing excellent mechanical properties, heat resistance and chemical stability, and are widely used in many fields. Aromatics (such as Kevlar) is a high-performance polyamide fiber with multiple aromatic ring structures, showing extremely high strength and heat resistance. Kevlar fiber is stronger and lighter than steel, can remain stable at extremely high temperatures, will not melt or deform, and has excellent tolerance to a variety of chemicals. This makes Kevlar widely used in the manufacture of personal protective equipment such as bulletproof vests and puncture-proof gloves, as well as in aerospace equipment and high-performance industrial products such as transmission belts and reinforced composites.

[0003] The preparation of aromatics into aromatic nanofibers has important scientific and application value. Aromatic fibers are widely used in protective equipment and aerospace fields due to their excellent strength, heat resistance and chemical resistance, such as Chinese patent publication numbers: CN117344549A, CN117551292A. However, with the development of science and technology, the demand for material performance is increasing, and single aromatic fibers can no longer meet higher application requirements. By preparing aromatics into nanofibers, their specific strength and specific modulus can be significantly improved, their performance under extreme conditions can be enhanced, and their adaptability to the microenvironment can be improved. Due to their high surface area to volume ratio, aromatic nanofibers have better mechanical properties, thermal stability and higher specific surface area, which makes them show broad application prospects in composite materials, functional coatings and high-performance textiles. However, their economy and sustainability in practical applications face challenges. First, the deprotonation process of aromatic nanofibers needs to be carried out in a strict chemical environment, involving complex chemical reactions and high energy consumption, resulting in high costs. This process not only increases production costs, but also limits the economic feasibility of their large-scale application. Secondly, aromatic nanofibers are extremely difficult to recycle, as their high chemical resistance and physical stability make it difficult for traditional recycling methods to effectively handle them. The recycling technology for this material is not yet mature, and the recycling process is cumbersome and costly, further exacerbating the environmental burden. Exploring the challenges of deprotonation and recycling of aromatic nanofibers is crucial to improving their economic and environmental sustainability. Summary of the invention

[0004] In view of the above problems, the object of the present invention is to provide a recyclable / redesigned aromatic nanofiber membrane / fiber and a preparation method thereof.

[0005] The technical solution of the present invention to solve the above technical problems is as follows:

[0006] The method for preparing a recyclable / redesigned aromatic nanofiber membrane / fiber comprises the following steps:

[0007] Step 1: dissolving aromatic fibers by using organic strong base, methanol and dimethyl sulfoxide to obtain aromatic nanofiber solution;

[0008] Step 2: Scrape or lay the aromatic nanofiber solution to obtain a nanofiber membrane, or obtain fibers by wet spinning, place the nanofiber membrane / fiber in a coagulation bath for solvent exchange, and obtain a dynamically bonded self-assembled aramid nanofiber membrane / fiber.

[0009] Furthermore, the aromatic fiber is para-aramid fiber, poly or polybenzimidazole or other aromatic fiber.

[0010] Furthermore, in step 1, the mass fractions of aromatic fiber, organic strong base, methanol and dimethyl sulfoxide are 4%, 5%, 5% and 86% respectively.

[0011] Furthermore, the organic strong base is any one of sodium alcoholate, potassium alcoholate or alkaline organic metal compounds such as potassium tert-butoxide, potassium methoxide, sodium methoxide and butyl lithium, and the kPa value is greater than 13.

[0012] Furthermore, in step 2, when preparing the nanofiber membrane, 10 mL of the aromatic nanofiber solution is scraped through a 500 μm four-sided preparation device, or directly poured into a 12 cm glass culture dish.

[0013] Furthermore, the coagulation bath contains deionized water, 0.5 wt % formic acid solution, 0.5 wt % acetic acid solution and 0.5 wt % ethyl acetate solution; the solvent exchange lasts for 24 hours, and the coagulation bath is reconfigured every 8 hours.

[0014] Furthermore, in step 2, when preparing nanofibers, the wet spinning needle is 20G and the spinning speed is 0.3 m / min.

[0015] The recyclable / redesigned aromatic nanofiber membrane / fiber is prepared by any of the methods described above.

[0016] The beneficial effects of the present invention are as follows: the present invention uses aromatic fiber as raw material, and uses organic strong base to deprotonate the amide bond on the molecular chain. And obtains a large amount of negative charge accumulation on the molecular chain, resulting in separation from the fiber body. That is, the organic strong base reacts with the amide bond on fibers such as poly(p-phenylene diamine) and Zylon, resulting in the removal of hydrogen atoms, followed by the release of cations, resulting in negatively charged amide bonds, so that the nanofiber solution is in a stable state. At the same time, deionized water, weak acid solution or hydrolyzed salts that present weak acidity provide protons to allow the aromatic nanofibers to undergo dynamic bond self-assembly to form a recyclable membrane material. The dynamic bond action in the nanofiber membrane of dynamic bond self-assembly is again destroyed by the above-mentioned organic strong base to achieve the effect of low cost and rapid recycling. And the recycled membrane material can be designed into fiber products and fabric products. This method provides a new idea for the recycling of some high-performance aromatic fibers. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 It is a schematic diagram of the method flow of the present invention;

[0018] Figure 2 Schematic diagram of the preparation mechanism of aromatic nanofiber solution;

[0019] Figure 3 Optical images of the aromatic nanofiber solution recovery process (left) and irradiation with a laser pointer (right);

[0020] Figure 4 This is an optical image of the recycled aromatic nanofibers.

[0021] Figure 5 is a scanning electron microscope image of the recycled aromatic nanofibers;

[0022] Figure 6 is a scanning electron microscope image of the recycled aromatic nanofibers;

[0023] Figure 7 Optical images of recycled aromatic nanofiber textiles. DETAILED DESCRIPTION

[0024] The principles and features of the present invention are described below in conjunction with specific embodiments. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.

[0025] like Figure 1 As shown, the preparation method of recyclable / redesigned aromatic nanofibrous membrane / fiber:

[0026] Step 1: dissolving aromatic fibers using organic strong base, methanol and dimethyl sulfoxide to obtain aromatic nanofiber solution;

[0027] Step 2: After the aromatic nanofiber solution is scraped or spread, it is placed in a coagulation bath for solvent exchange to achieve dynamic bond self-assembly of the aramid nanofibers;

[0028] Step 3, vacuum drying the obtained aromatic nanofiber hydrogel to obtain an aromatic nanofiber membrane;

[0029] Step 4: Recycling after use, dissolving the aromatic nanofiber membrane using potassium tert-butoxide, methanol and dimethyl sulfoxide to obtain a recycled aromatic nanofiber solution;

[0030] Step 5: Use wet spinning technology to spin the recovered aromatic nanofiber solution into fibers, dry them, and reuse them.

[0031] Specifically, in the step 1, the mass proportions of aromatic fiber, organic strong base, methanol and dimethyl sulfoxide in the dispersion are 4%, 5%, 5% and 86%, respectively. The aromatic fiber can be para-aramid fiber, Zylon and other aromatic fibers. The organic strong base can be: potassium tert-butoxide, potassium methoxide, sodium methoxide, sodium ethoxide, butyl lithium, lithium diisopropylamide, benzyl lithium and other sodium alcohols, potassium alcohols and alkaline organic metal compounds, and their kPa values ​​are at least greater than 13.

[0032] Specifically, in the step 2, 10 mL of the aromatic nanofiber solution is scraped through a 500 μm four-sided preparation device, or directly poured into a 12 cm glass culture dish. The coagulation bath used can be: deionized water, 0.5 wt% formic acid solution, 0.5 wt% acetic acid solution, 0.5 wt% ethyl acetate solution. The solvent is exchanged for 24 hours, and the coagulation bath is reconfigured every 8 hours.

[0033] Specifically, in step three, the temperature of the vacuum oven is maintained at about 50-60° C., and the drying is performed for 4-5 hours.

[0034] Specifically, in step 4, the mass proportions of aromatic fiber, potassium tert-butoxide, methanol and dimethyl sulfoxide in the dispersion are 2%, 5%, 5% and 88%, respectively. The aromatic fiber can be para-aramid fiber, Zylon and other aromatic fibers.

[0035] Specifically, in step 5, the wet spinning needle is 20G, the spinning speed is 0.3 m / min, and the coagulation bath may be: deionized water, 0.5 wt% formic acid solution, 0.5 wt% acetic acid solution, 0.5 wt% ethyl acetate solution. The drying condition is drying at 40° C. for 4 hours.

[0036] Embodiment 1:

[0037] A method for preparing a recyclable / redesigned aromatic nanofiber membrane / fiber, the preparation method comprising:

[0038] Step 1: Dissolve 4 g of Kevlar 49 using 5 g of potassium tert-butoxide, 5 g of methanol and 86 g of dimethyl sulfoxide, and stir at room temperature for 2 h to obtain an aramid nanofiber solution;

[0039] Step 2: 10 mL of aramid nanofiber solution was scraped with a 500 μm four-sided preparation device and placed in deionized water for solvent exchange to achieve dynamic bond self-assembly of the aramid nanofiber;

[0040] Step 3, drying the obtained aramid nanofiber hydrogel in a vacuum oven at 60° C. for 4 h to obtain an aramid nanofiber membrane;

[0041] Step 4: Recycling after use: dissolving 4 g of aramid nanofiber membrane with 5 g of potassium tert-butoxide, 5 g of methanol and 86 g of dimethyl sulfoxide, stirring at room temperature for 6 h to obtain a recycled aramid nanofiber solution;

[0042] Step 5: Use wet spinning technology to spin the recovered aramid nanofiber solution into fibers and then dry them. The wet spinning needle is 20G, the spinning speed is 0.3m / min, and the coagulation bath is deionized. The drying condition is 40°C for 4 hours.

[0043] Embodiment 2:

[0044] A method for preparing a recyclable / redesigned aromatic nanofiber membrane / fiber, the preparation method comprising:

[0045] Step 1: Dissolve 4 g of Kevlar 49 using 5 g of potassium tert-butoxide, 5 g of methanol and 86 g of dimethyl sulfoxide, and stir at room temperature for 2 h to obtain an aramid nanofiber solution;

[0046] Step 2: 10 mL of aramid nanofiber solution was scraped with a 500 μm four-sided preparation device and placed in a 0.5 wt % formic acid solution for solvent exchange to achieve dynamic bond self-assembly of the aramid nanofiber;

[0047] Step 3, drying the obtained aramid nanofiber hydrogel in a vacuum oven at 60° C. for 4 h to obtain an aramid nanofiber membrane;

[0048] Step 4: Recycling after use: dissolving 4 g of aramid nanofiber membrane with 5 g of potassium tert-butoxide, 5 g of methanol and 86 g of dimethyl sulfoxide, stirring at room temperature for 6 h to obtain a recycled aramid nanofiber solution;

[0049] Step 5: Use wet spinning technology to spin the recovered aramid nanofiber solution into fibers and then dry them. The wet spinning needle is 20G, the spinning speed is 0.3m / min, and the coagulation bath is a 0.5wt% formic acid solution. The drying condition is 40°C for 4h.

[0050] Embodiment three:

[0051] A method for preparing a recyclable / redesigned aromatic nanofiber membrane / fiber, the preparation method comprising:

[0052] Step 1: Dissolve 4 g of Kevlar 49 using 5 g of potassium tert-butoxide, 5 g of methanol and 86 g of dimethyl sulfoxide, and stir at room temperature for 2 h to obtain an aramid nanofiber solution;

[0053] Step 2: 10 mL of aramid nanofiber solution was scraped with a 500 μm four-sided preparation device and placed in a 0.5 wt % acetic acid solution for solvent exchange to achieve dynamic bond self-assembly of the aramid nanofiber;

[0054] Step 3, drying the obtained aramid nanofiber hydrogel in a vacuum oven at 60° C. for 4 h to obtain an aramid nanofiber membrane;

[0055] Step 4: Recycling after use: dissolving 4 g of aramid nanofiber membrane with 5 g of potassium tert-butoxide, 5 g of methanol and 86 g of dimethyl sulfoxide, stirring at room temperature for 6 h to obtain a recycled aramid nanofiber solution;

[0056] Step 5: Use wet spinning technology to spin the recovered aramid nanofiber solution into fibers and then dry them. The wet spinning needle is 20G, the spinning speed is 0.3m / min, and the coagulation bath is a 0.5wt% acetic acid solution. The drying condition is 40°C for 4h.

[0057] Embodiment 4:

[0058] A method for preparing a recyclable / redesigned aromatic nanofiber membrane / fiber, the preparation method comprising:

[0059] Step 1: Dissolve 4 g of Kevlar 49 using 5 g of potassium tert-butoxide, 5 g of methanol and 86 g of dimethyl sulfoxide, and stir at room temperature for 2 h to obtain an aramid nanofiber solution;

[0060] Step 2: 10 mL of aramid nanofiber solution was scraped with a 500 μm four-sided preparation device and placed in a 0.5 wt % ethyl acetate solution for solvent exchange to achieve dynamic bond self-assembly of the aramid nanofiber;

[0061] Step 3, drying the obtained aramid nanofiber hydrogel in a vacuum oven at 60° C. for 4 h to obtain an aramid nanofiber membrane;

[0062] Step 4: Recycling after use: dissolving 4 g of aramid nanofiber membrane with 5 g of potassium tert-butoxide, 5 g of methanol and 86 g of dimethyl sulfoxide, stirring at room temperature for 6 h to obtain a recycled aramid nanofiber solution;

[0063] Step 5: Use wet spinning technology to spin the recovered aramid nanofiber solution into fibers and then dry them. The wet spinning needle is 20G, the spinning speed is 0.3m / min, and the coagulation bath is a 0.5wt% ethyl acetate solution. The drying condition is 40°C for 4h.

[0064] Embodiment five:

[0065] A method for preparing a recyclable, redesignable aromatic nanofiber membrane / fiber, the preparation method comprising:

[0066] Step 1: Dissolve 4 g of Kevlar 49 using 5 g of potassium tert-butoxide, 5 g of methanol and 86 g of dimethyl sulfoxide, and stir at room temperature for 2 h to obtain an aramid nanofiber solution;

[0067] Step 2: Pour 10 mL of the aramid nanofiber solution into a 12 cm diameter watch glass, and place it in deionized water for solvent exchange to achieve dynamic bond self-assembly of the aramid nanofibers;

[0068] Step 3, drying the obtained aramid nanofiber hydrogel in a vacuum oven at 60° C. for 4 h to obtain an aramid nanofiber membrane;

[0069] Step 4: Recycling after use: dissolving 4 g of aramid nanofiber membrane with 5 g of potassium tert-butoxide, 5 g of methanol and 86 g of dimethyl sulfoxide, stirring at room temperature for 6 h to obtain a recycled aramid nanofiber solution;

[0070] Step 5: Use wet spinning technology to spin the recovered aramid nanofiber solution into fibers and then dry them. The wet spinning needle is 20G, the spinning speed is 0.3m / min, and the coagulation bath is deionized. The drying condition is 40°C for 4 hours.

[0071] Embodiment six:

[0072] A method for preparing a recyclable, redesignable aromatic nanofiber membrane / fiber, the preparation method comprising:

[0073] Step 1: Dissolve 4 g of Kevlar 49 with 5 g of potassium methoxide, 5 g of methanol and 86 g of dimethyl sulfoxide, and stir at room temperature for 2 h to obtain an aramid nanofiber solution;

[0074] Step 2: Pour 10 mL of the aramid nanofiber solution into a 12 cm diameter watch glass, and place it in deionized water for solvent exchange to achieve dynamic bond self-assembly of the aramid nanofibers;

[0075] Step 3, drying the obtained aramid nanofiber hydrogel in a vacuum oven at 60° C. for 4 h to obtain an aramid nanofiber membrane;

[0076] Step 4: Recycling after use: dissolving 4 g of aramid nanofiber membrane with 5 g of potassium methoxide, 5 g of methanol and 86 g of dimethyl sulfoxide, stirring at room temperature for 6 h, and obtaining a recycled aramid nanofiber solution;

[0077] Step 5: Use wet spinning technology to spin the recovered aramid nanofiber solution into fibers and then dry them. The wet spinning needle is 20G, the spinning speed is 0.3m / min, and the coagulation bath is deionized. The drying condition is 40°C for 4 hours.

[0078] Embodiment seven:

[0079] A method for preparing a recyclable / redesigned aromatic nanofiber membrane / fiber, the preparation method comprising:

[0080] Step 1: Dissolve 4 g of Zylon in 5 g of potassium tert-butoxide, 5 g of methanol and 86 g of dimethyl sulfoxide, and stir at room temperature for 2 h to obtain a Zylon nanofiber solution;

[0081] Step 2: 10 mL of Zylon nanofiber solution was scraped with a 500 μm four-sided preparation device and placed in deionized water for solvent exchange to achieve dynamic bond self-assembly of Zylon nanofibers;

[0082] Step 3: drying the obtained Zylon nanofiber hydrogel in a vacuum oven at 60°C for 4 hours to obtain an aramid nanofiber membrane;

[0083] Step 4: Recycling after use: dissolving 4 g of Zyl on nanofiber membrane with 5 g of potassium tert-butoxide, 5 g of methanol and 86 g of dimethyl sulfoxide, stirring at room temperature for 6 h to obtain a recycled aramid nanofiber solution;

[0084] Step 5: Use wet spinning technology to spin the recovered Zylon nanofiber solution into fibers and then dry them. The wet spinning needle is 20G, the spinning speed is 0.3m / min, and the coagulation bath is ionized water. The drying condition is 40°C for 4h.

[0085] Embodiment eight:

[0086] A method for preparing a recyclable / redesigned aromatic nanofiber membrane / fiber, the preparation method comprising:

[0087] Step 1: dissolve 4 g of polybenzimidazole in 5 g of potassium tert-butoxide, 5 g of methanol and 86 g of dimethyl sulfoxide, and stir at room temperature for 2 h to obtain a polybenzimidazole nanofiber solution;

[0088] Step 2: 10 mL of polybenzimidazole nanofiber solution was scraped with a 500 μm four-sided preparation device and placed in deionized water for solvent exchange to achieve dynamic bond self-assembly of polybenzimidazole nanofibers;

[0089] Step 3, drying the obtained polybenzimidazole nanofiber hydrogel in a vacuum oven at 60° C. for 4 h to obtain an aramid nanofiber membrane;

[0090] Step 4: Recycling after use: dissolving 4 g of polybenzimidazole nanofiber membrane with 5 g of potassium tert-butoxide, 5 g of methanol and 86 g of dimethyl sulfoxide, stirring at room temperature for 6 h to obtain a recycled aramid nanofiber solution;

[0091] Step 5: Use wet spinning technology to spin the recovered polybenzimidazole nanofiber solution into fibers and then dry them. The wet spinning needle is 20G, the spinning speed is 0.3m / min, and the coagulation bath is ionized water. The drying condition is 40°C for 4h.

[0092] In the above specific examples, compared with specific examples 1, 7 and 8, para-aramid, poly(p-phenylene-2,6-benzisoxazole), polybenzimidazole and other fibers can be destroyed by strong organic bases to obtain nanofiber solutions. Compared with specific examples 1 and 6, strong organic bases include potassium alcoholate, sodium alcoholate and alkaline organic metal compounds with kPa greater than 13, and the efficiency of Example 1 using potassium tert-butoxide is the fastest. Compared with specific examples 1, 2, 3 and 4, deionized water, weak acid solution or hydrolyzed weakly acidic salts provide protons to allow aromatic nanofibers to undergo dynamic bond self-assembly to form recyclable membrane materials, and the recyclable membrane induced by ethyl acetate in Example 4 has the best mechanical properties. During the recycling process, the use of pre-used solvents can avoid material contamination and waste. Among the recycled fibers of wet spinning, the fibers induced by ethyl acetate self-assembly have the best mechanical properties.

[0093] like Figure 1 As shown, taking aramid as an example, potassium tert-butoxide / methanol is ionized into an organic strong base in dimethyl sulfoxide to destroy the amide bond of the aramid fiber, thereby obtaining a wine-red aramid nanofiber solution, which is then passed through a coagulation bath of deionized water / formic acid / acetic acid / ethyl acetate. The protons provided by the coagulation bath accelerate the hydrogen bond self-assembly of the aramid nanofiber. Since hydrogen bonds are dynamic, the obtained aramid nanofiber membrane can be destroyed again by potassium tert-butoxide / methanol, thereby achieving the effect of re-collection;

[0094] like Figure 2As shown, taking aramid as an example, potassium tert-butoxide / methanol deprotonates the amide bonds on the molecular chain. And a large amount of negative charge accumulation on the molecular chain is obtained, resulting in separation from the fiber body. That is, potassium tert-butoxide / methanol reacts with the amide bonds on aramid, resulting in the removal of hydrogen atoms, followed by the release of potassium ions, resulting in negatively charged amide bonds, which stabilizes the nanofiber solution;

[0095] like Figure 3 As shown, taking aramid as an example, the aramid nanofiber membrane was recovered in potassium tert-butoxide, methanol, and dimethyl sulfoxide solvents, and the recovered aramid nanofiber solution had good dispersion and stability. After being irradiated by a laser pen, a stable optical fiber appeared, and no obvious scattering phenomenon occurred, further indicating that the recovered aramid nanofiber solution had good dispersion and stability.

[0096] like Figure 4 As shown, taking aramid as an example, the recycled aramid nanofiber-based fibers and aramid nanofiber-based fibers have similar colors, showing a light yellow and uniform color without obvious pilling;

[0097] like Figure 5 As shown, taking aramid as an example, the recycled aramid nanofiber-based fibers show good flexibility and can be knotted.

[0098] like Figure 6 As shown, taking aramid as an example, the recycled aramid nanofiber-based fibers exhibit good mechanical properties, with a breaking strength of 60 mPa.

[0099] like Figure 7 As shown, taking aramid as an example, the recycled aramid nanofiber-based fibers can be woven into fabrics.

[0100] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a recyclable / redesigned aromatic nanofiber membrane / fiber, characterized in that: The specific steps include: Step 1: dissolving aromatic fibers by using organic strong base, methanol and dimethyl sulfoxide to obtain aromatic nanofiber solution; Step 2: Scrape or lay the aromatic nanofiber solution to obtain a nanofiber membrane, or obtain fibers by wet spinning, place the nanofiber membrane / fiber in a coagulation bath for solvent exchange, and obtain a dynamically bonded self-assembled aramid nanofiber membrane / fiber.

2. The method for preparing the recyclable / redesigned aromatic nanofiber membrane / fiber according to claim 1, characterized in that: The aromatic fiber is para-aramid fiber, poly or polybenzimidazole and other aromatic fibers.

3. The method for preparing the recyclable / redesigned aromatic nanofiber membrane / fiber according to claim 1, characterized in that: In the step 1, the mass fractions of the aromatic fiber, the organic strong base, methanol and dimethyl sulfoxide are 4%, 5%, 5% and 86% respectively.

4. The method for preparing the recyclable / redesigned aromatic nanofiber membrane / fiber according to claim 1, characterized in that: The organic strong base is any one of sodium alcoholate, potassium alcoholate or alkaline organic metal compounds such as potassium tert-butoxide, potassium methoxide, sodium methoxide and butyl lithium, and the kPa value is greater than 13.

5. The method for preparing the recyclable / redesigned aromatic nanofiber membrane / fiber according to claim 1, characterized in that: In the step 2, when preparing the nanofiber membrane, 10 mL of the aromatic nanofiber solution is scraped through a 500 μm four-sided preparation device, or directly poured into a 12 cm glass culture dish.

6. The method for preparing the recyclable / redesigned aromatic nanofiber membrane / fiber according to claim 1, characterized in that: The coagulation bath contained deionized water, 0.5 wt % formic acid solution, 0.5 wt % acetic acid solution and 0.5 wt % ethyl acetate solution; the solvent exchange lasted for 24 h, and the coagulation bath was reconfigured every 8 h.

7. The method for preparing the recyclable / redesigned aromatic nanofiber membrane / fiber according to claim 1, characterized in that: In the step 2, when preparing nanofibers, the wet spinning needle is 20G and the spinning speed is 0.3 m / min.

8. Recyclable / redesigned aromatic nanofiber membrane / fiber, characterized in that: Prepared by the method according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Aramid nanofiber-based insulation paper and preparation method thereof

    CN110485195A

  • Preparation method of aramid nano-fiber dispersion liquid

    CN112409613A

  • Recyclable aramid nanofiber aerogel as well as preparation method and application thereof

    CN115850787A

  • Process to make an aramid solution

    WO2024079027A2